The influence of transformational leadership and organizational commitment on employee performance of tea distributor - Gusti, Rizka Pamuji; Wangi, Putri Sekar; Nofiantari, Putri; Hardjowikarto, Dharliana; Kartono, Kartono (International Journal Labs, 2024)
This study focuses on the impact of transformational leadership, organizational culture, and organizational commitment on employee performance of Javanese tea distributors. The research methodology is quantitative, involving 115 individuals from the Java Tea Distributor. Data collection was done through questionnaires, which were used to assess factors such as transformational leader, organizational commitment, and employee performance. The reliability of Partial Least Squares (PLS) analysis was assessed in this study using the Cronbach Alpha, Composite Reliability, and Average Variance Extracted (AVE) methods. The results showed that Transformational Leadership has an indirect influence on Employee Performance through its influence on Organizational Commitment. The study reveals that organizational commitment has a significant impact on the performance of the Javan tea distributor personnel using the SmartPLS application.